Modified posterior vertebral column resection for Kümmell disease: Case report. Issue 5 (February 2017) - Liu, Feng-Yu; Huo, Li-Shuang; Liu, Sen; Wang, Hui; Zhang, Li-Jun; Yang, Da-Long; Ding, Wen-Yuan
Abstract: Rationale: Kümmell's disease is defined as delayed traumatic vertebral collapse disease in which patients develop a kyphosis after asymptomatic minor spinal trauma. Both anterior approach and posterior approach have been reported, however, there is no standard treatment for Kümmell's disease. Patient concerns: We described a successful modified posterior vertebral column resection in a patient with Kümmell's disease. A 65-year-old woman reported persistent back pain for almost three months. Diagnoses: Kümmell's disease was diagnosed based on computer tomography (CT) and magnetic resonance imaging (MRI). Interventions: Modified posterior vertebral column resection combined with short-segment fixation was designed to treat this disease. Outcomes: The procedure was successful without any complications. Patient reported that symptoms were obviously improved in one week after operation. Lessons: Modified posterior vertebral column resection combined with short-segment fixation is an effective treatment option for Kümmell's disease.